Method for preparing Al-Al2O3-TPU mixed corrosion-resistant coating through low-pressure cold spraying and application of Al-Al2O3-TPU mixed corrosion-resistant coating
Through low-pressure cold spraying technology, Al powder, Al2O3 ceramic particles and TPU powder are mixed and sprayed, which solves the problems of pores and cracks in traditional coating preparation technology, and achieves efficient and environmentally friendly coating preparation, which is suitable for harsh environments such as marine engineering.
Patent Information
- Application Number
- CN202411536724.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Traditional corrosion-resistant coating preparation technology has problems of pores and cracks, and the high-temperature spraying process consumes high energy and is seriously polluted, making it difficult to meet the demands of harsh environments such as marine engineering.
Low-pressure cold spraying technology is used to mechanically mix Al powder, Al2O3 ceramic particles and TPU powder, and low-pressure cold spraying is applied to the substrate to form an Al-Al2O3-TPU mixed corrosion-resistant coating.
It realizes the preparation of dense and uniform coatings at lower temperatures, improves the adhesion and corrosion resistance of the coating, reduces energy consumption and environmental pollution, and is suitable for various application environments such as marine engineering.
Smart Images

Figure CN119663266A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface engineering, and specifically relates to a method for preparing Al-Al by low-pressure cold spraying. 2 O 3 -TPU hybrid corrosion resistant coating method and its application. Background Art
[0002] In the field of surface additive remanufacturing, the development and application of corrosion-resistant coatings have received widespread attention. This is because corrosion-resistant coatings can effectively protect the substrate, extend its service life, reduce maintenance costs, and improve economic benefits. Among various metal materials, Al metal is widely used in various industrial fields such as chemical, petroleum, and marine industries due to its excellent corrosion resistance. However, there are many problems with the traditional corrosion-resistant coating preparation technology, such as the generation of pores and cracks, and higher spraying problems causing deformation of the metal substrate, phase change, and thermal stress damage. In order to solve this problem, many scholars have studied methods to improve the quality of coatings from different aspects, such as selecting appropriate coating preparation methods and continuously optimizing the process to improve the quality of coatings, and introducing suitable filling materials to seal the pores and defects in the coating to improve the quality of the coating, thereby improving the corrosion resistance.
[0003] Traditional coating preparation methods, such as thermal spraying and electroplating, usually require high energy consumption to generate high temperatures to make the metal material molten or semi-molten, and then spray it onto the surface of the substrate with high-speed airflow to cause thermoplastic deformation and cooling, forming a layered coating. Due to its inherent technical limitations, there are many defects in the prepared coating, such as pores, cracks, and unmelted particles. These defects can serve as transmission channels for corrosive media in actual working conditions. The corrosive media can penetrate into the interior of the substrate and cause corrosion of the equipment, reducing the service life of the equipment. In addition, traditional coating preparation technology also has a complex process flow and is prone to environmental pollution. Therefore, it is necessary to find a low-energy, environmentally friendly coating preparation method. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a low-pressure cold spraying method for preparing Al-Al 2 O 3 -TPU mixed corrosion-resistant coating method and its application, the coating can be applied to marine engineering environment and can resist seawater erosion and corrosion.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a low-pressure cold spraying method for preparing Al-Al 2 O 3 -TPU mixed corrosion resistant coating method, the method is:
[0006] S1. Substrate preparation: The substrate is subjected to surface treatment, and is sequentially ground, polished, cleaned, dried, and sandblasted to obtain a substrate to be sprayed;
[0007] S2, Al powder, Al 2 O 3 The ceramic particles and thermoplastic polyurethane TPU powder are mechanically mixed to obtain cold spray prefabricated powder;
[0008] S3, low-pressure cold spraying the preformed powder obtained in S2 onto the substrate to be sprayed obtained in S1, and after the coating is cooled and solidified, grinding and correction are performed to obtain Al-Al 2 O 3 -TPU hybrid corrosion resistant coating;
[0009] The process parameters of the low-pressure cold spraying are: the working gas is compressed air, the carrier gas pressure is 0.2-0.5 MPa, the carrier gas temperature is 150-200° C., the nozzle is 10-20 mm away from the substrate, and the spraying speed is 30-60 g / min.
[0010] Preferably, the substrate in S1 is 316L stainless steel material.
[0011] Preferably, the Al powder in S2 is a nearly spherical powder with a particle size of 10 μm to 40 μm and a purity of ≥99.9%; 2 O 3 The ceramic particles are irregular particles with a particle size of 20 μm to 50 μm and a purity of ≥ 99.9%; the thermoplastic polyurethane TPU powder has a particle size of 20 μm to 50 μm and a purity of ≥ 99.9%.
[0012] Preferably, the cold spray preformed powder in S2 is composed of the following raw materials by mass fraction: 35% Al powder, 2 O 3 Ceramic particles 35%, the rest is thermoplastic polyurethane TPU powder.
[0013] Preferably, the mechanical mixing time in S2 is 8 hours.
[0014] Preferably, the Al-Al in S3 2 O 3 -The average thickness of the TPU hybrid corrosion-resistant coating is 500μm to 2mm.
[0015] Preferably, the Al-Al in S3 2 O 3 -TPU mixed corrosion-resistant coating has an annual average immersion corrosion rate of 0.011-0.012 mm / a, and an annual average erosion corrosion rate of 0.012-0.013 mm / a; the Al-Al 2 O3 -TPU hybrid corrosion resistant coating and substrate bonding strength is 23.62 ~ 26.36MPa, the Al-Al 2 O 3 -The porosity of the TPU mixed corrosion-resistant coating is 2.35% to 2.67%.
[0016] The present invention also provides Al-Al prepared by the above method. 2 O 3 -Application of TPU hybrid corrosion resistant coating, the Al-Al 2 O 3 -TPU hybrid corrosion resistant coating for marine engineering.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] The present invention comprises Al metal powder, Al 2 O 3 Ceramic particles and polymer TPU are combined to create a composite coating with multiple excellent properties. Each material plays a unique role in the coating, providing a comprehensive protective effect. The use of low-pressure cold spray technology to prepare this composite coating can achieve efficient deposition of the coating at a lower temperature, reduce the impact of thermal stress on the substrate and coating, and improve the adhesion and overall performance of the coating. The prepared coating not only has excellent mechanical strength and corrosion resistance, but also has good thermal stability and toughness, and is suitable for a variety of harsh application environments.
[0019] The present invention utilizes low-pressure cold spraying to prepare Al-Al 2 O 3 -TPU hybrid coating has good adhesion, low porosity, excellent corrosion resistance, and avoids the problem of thermal damage to the substrate caused by traditional high-temperature thermal spraying. Compared with the existing technology, the advantages are mainly as follows:
[0020] (1) Improve coating density and uniformity
[0021] Selecting a TPU powder particle size within the range of 20 to 50 μm ensures the fluidity and deposition efficiency of the powder during spraying, thereby forming a uniform and dense coating; spraying is carried out within the optimal temperature range of 150 to 200 ° C, which not only ensures the plastic deformation of the Al metal powder, but also ensures the full melting and filling of the TPU powder, significantly improving the density and surface smoothness of the coating.
[0022] (2) Enhance the mechanical properties and corrosion resistance of the coating
[0023] Using TPU powder with a purity of ≥99.9% ensures the stability and corrosion resistance of the coating in high temperature and marine environments, extending the service life of the coating; by designing a suitable coating material ratio, it not only has good mechanical strength and toughness, but also has excellent wear resistance and impact resistance, and is suitable for a wider range of application scenarios.
[0024] (3) Energy conservation and environmental protection
[0025] Compared with traditional thermal spraying methods, cold spraying technology can achieve efficient coating preparation at lower temperatures, reduce energy consumption, and reduce thermal pollution to the environment and the risk of metal powder oxidation.
[0026] (4) Adapt to various application environments
[0027] Using Al-Al 2 O 3 -TPU mixed material, the coating formed has good comprehensive properties such as seawater corrosion resistance, high temperature resistance, wear resistance and high strength, and is suitable for various application fields such as ocean, aviation, and chemical industry.
[0028] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The Al-Al of Example 1 2 O 3 SEM image of mixed preformed powder.
[0030] Figure 2 This is a physical picture of the TPU powder of Example 1.
[0031] Figure 3 The Al-Al prepared in Example 1 2 O 3 -Pore test distribution diagram of TPU hybrid corrosion resistant coating.
[0032] Figure 4 The Al-Al prepared in Example 1 of the present invention 2 O 3 -Seawater immersion corrosion and erosion corrosion rate diagram of TPU hybrid corrosion-resistant coating.
[0033] Figure 5 The Al-Al prepared in Example 1 of the present invention 2 O 3 -Microscopic image of the TPU hybrid corrosion-resistant coating, including (a) surface SEM image and (b) cross-sectional schematic diagram. DETAILED DESCRIPTION
[0034] Example 1
[0035] The low pressure cold spraying method of this embodiment is used to prepare Al-Al 2 O 3 -TPU mixed corrosion resistant coating method, the method is:
[0036] S1. Substrate preparation: The aluminum-based material is surface treated by grinding, polishing, cleaning, drying and sandblasting in sequence to obtain the substrate to be sprayed; the preliminary treatment of the substrate can ensure that the substrate surface is clean, dry and roughened, and enhance the adhesion of the coating.
[0037] S2, Al powder, Al 2 O 3 The ceramic particles and thermoplastic polyurethane TPU powder are mechanically mixed for 8 hours to obtain a cold spray preformed powder;
[0038] Al powder and Al 2 O 3 After mixing the ceramic particles, the Al-Al 2 O 3 SEM images of mixed preformed powders are shown in Figure 1 , Al powder is a nearly spherical powder with a particle size of 10μm to 40μm (purity ≥99.9%), Al 2 O 3 Ceramic particles are irregular particles with a particle size of 20μm to 50μm (purity ≥ 99.9%, oxygen content O 2 ≤300ppm); Thermoplastic polyurethane TPU powder has a particle size of 20μm to 50μm and a purity of ≥99.9% ( Figure 2 ); The cold spray preformed powder is composed of the following raw materials by mass fraction: 35% Al powder, Al 2 O 3 35% ceramic particles, the rest is thermoplastic polyurethane TPU powder;
[0039] Thermoplastic polyurethane TPU powder was purchased from Huafeng Thermoplastic Polyurethane Co., Ltd.
[0040] In this embodiment, the particle size of each raw material in the cold spray preformed powder is small, which ensures the fluidity and deposition efficiency of the powder during the spraying process, thereby forming a uniform and dense coating. It is not only suitable for cold spraying technology, but can also effectively improve the deposition rate and fill the tiny pores in the Al coating. Moreover, the smaller particle size can improve the flatness of the coating surface and reduce the roughness of the coating.
[0041] The use of high-purity TPU powder ensures the stability and corrosion resistance of the coating in high temperature and marine environments, extending the service life of the coating; by designing a suitable coating material ratio, it not only has good mechanical strength and toughness, but also has excellent wear resistance and impact resistance, and is suitable for a wider range of application scenarios.
[0042] S3, cold spraying the cold spray prefabricated powder obtained in S2 onto the substrate to be sprayed obtained in S1 at low pressure, and after the coating is cooled and solidified, grinding and correction are performed to obtain an Al-Al with an average thickness of 500 μm. 2 O 3 -TPU hybrid corrosion resistant coating;
[0043] The process parameters of the low-pressure cold spraying are as follows: the working gas is compressed air, the carrier gas pressure is 0.5 MPa, the carrier gas temperature is 150°C, the nozzle is 10 mm away from the substrate, and the spraying speed is 30 g / min. During the cold spraying process, the Al powder undergoes plastic deformation at high temperature and high speed and meshes with the substrate. 2 O 3 Ceramic particles serve as a reinforcing composite material to improve the hardness and strength of the coating. The TPU powder is melted, wetted and cooled to build a sealing layer during the spraying process to fill the pores and defects of the Al-based coating, thereby enhancing the overall corrosion resistance of the coating.
[0044] The spraying of this embodiment is carried out at a low temperature (150° C.), which will not damage the substrate and the polymer, and ensures both the plastic deformation of the Al metal powder and the full melting and filling of the TPU powder, thereby significantly improving the density and surface smoothness of the coating.
[0045] Compared with traditional thermal spraying methods, cold spraying technology can achieve efficient coating preparation at lower temperatures, reduce energy consumption, and reduce thermal pollution to the environment and the risk of metal powder oxidation.
[0046] Al-Al 2 O 3 -The main functions of each element in the TPU mixed corrosion-resistant coating are as follows:
[0047] Function of Al element:
[0048] (1) Enhanced mechanical properties
[0049] As a metal material, Al has high hardness and strength, which can improve the hardness and strength of the overall coating and improve its impact resistance and wear resistance.
[0050] (2) Improve corrosion resistance
[0051] Al can quickly form a dense layer of Al in the air. 2 O 3 The film has good chemical stability and excellent corrosion resistance to a variety of acids, alkalis and salt solutions, which enables the coating to work stably for a long time in harsh chemical environments and can effectively prevent further corrosion of the substrate by oxygen and moisture.
[0052] (3) Enhance coating toughness
[0053] The toughness of Al can make the coating less likely to crack when subjected to mechanical stress or thermal stress. When subjected to impact or vibration, the presence of Al can provide a certain buffering effect, protecting the substrate from damage and thus extending the service life of the coating.
[0054] Al 2 O 3 Ceramic particles function:
[0055] (1) Ceramic particles have extremely high hardness, and adding them into the coating can significantly improve the overall hardness and wear resistance of the coating.
[0056] (2) It has excellent chemical stability and can effectively resist the erosion of corrosive media in the marine environment.
[0057] (3) Ceramic particles can fill tiny defects and pores in the coating, increase the density of the coating, and thus improve the overall performance of the coating.
[0058] (3) It has good thermal stability and can maintain its physical and chemical properties in a high temperature environment, thus enhancing the stability of the coating under high temperature conditions.
[0059] TPU function:
[0060] (1) Function of binder:
[0061] As a binder, TPU can effectively combine aluminum-based materials and alumina ceramic particles to form a uniform and dense coating structure. Its excellent bonding performance ensures the overall stability and durability of the coating.
[0062] (2) Flexibility:
[0063] TPU has excellent flexibility, which can effectively compensate for the brittleness of aluminum-based coatings. This flexibility enables the coating to absorb energy when impacted or deformed, reducing the generation of cracks.
[0064] (3) Compatibility with Al:
[0065] The good compatibility between TPU and Al-based materials enables them to form a stable bonding interface and enhance the adhesion of the coating. This bonding is critical to the overall performance of the coating, especially under dynamic loads or in corrosive environments.
[0066] (6) Excellent chemical corrosion resistance and wear resistance:
[0067] The chemical structure of TPU makes it have good chemical corrosion resistance and can resist the erosion of corrosive media such as seawater and salt spray. In addition, TPU has good wear resistance, which can improve the wear resistance of the coating and extend the service life of the coating.
[0068] In order to analyze the seawater corrosion resistance of the coating, two different experimental methods, immersion corrosion and scouring corrosion, were used to test the corrosion resistance of the coating samples. Three parallel samples were used in each set of experiments. Before the test, the polished samples were ultrasonically cleaned and then placed in a drying oven for drying. In the immersion corrosion experiment, the sample blocks were immersed in a 3.5wt% NaCl solution for 180 hours. In order to simulate a more severe corrosion environment, the corrosive solution was replaced every 48 hours. The scouring corrosion experiment was carried out in accordance with GB10124-1988 standard. The seawater scouring corrosion experiment was carried out in accordance with GB10124-1988 standard. The corrosive medium contained 3.5wt% NaCl and 7.62kg / m 3 A solution of mud and sand. In order to ensure the fluidity of the corrosive medium, the agitation was increased by an electric propeller in the experiment, the liquid flow rate reached 5m / s, and the corrosion time was set to 180h. To ensure the accuracy of the detection, the detection surface of the coating sample was in full contact with the corrosive medium, while the other surfaces were coated with epoxy resin to isolate the corrosion. The sample was embedded in the disc of the scouring corrosion device, completely immersed in the corrosive medium, and tested under stirring conditions. The main goal of the experiment was to evaluate the corrosion depth (or amount of corrosion) and the corrosion rate of the coating. After the experiment was completed, an electronic balance with an accuracy of 0.0001g was used to measure the weight change of the sample before and after corrosion to calculate the corrosion rate.
[0069] At the same time, Al single-element coating was prepared by the same cold spraying technology as a control group to compare and illustrate the effect of Al-Al 2 O 3 -Advantages of TPU hybrid coating.
[0070] The Al-Al prepared in this example 2 O 3 -The annual average immersion corrosion rate of the TPU hybrid corrosion-resistant coating is 0.011mm / a, and the annual average erosion corrosion rate is 0.012mm / a.
[0071] like Figure 3 As shown, the porosity analysis of the coating surface SEM image was performed using Image J analysis software. The distribution of defective pores is shown in the red area in the figure. The porosity size is calculated based on the pore ratio, that is, porosity = (pore area / coating total area) × 100%. The calculated Al-Al prepared in this embodiment 2 O 3 -The porosity of the TPU hybrid corrosion-resistant coating is 2.67%.
[0072] The coating prepared by thermal spraying of alloy coating powder has a porosity of about 10%, such as Al-Al 2 O 3The porosity of the coating is as high as 10% to 15%. High porosity may lead to a decrease in the anti-corrosion and wear resistance of the coating. In addition, thermal spraying may cause oxidation and decarburization of the substrate, and oxide impurities in the coating, which may affect the quality and service life of the coating. 2 O 3 -TPU hybrid coating has good adhesion, low porosity, and excellent corrosion resistance, while avoiding the problems of thermal oxidation and substrate thermal damage that may be caused by traditional high-temperature thermal spraying.
[0073] The Al-Al prepared in this example 2 O 3 -TPU hybrid corrosion-resistant coating has good comprehensive properties such as seawater corrosion resistance, high temperature resistance, wear resistance and high strength, and is suitable for various application fields such as ocean, aviation, and chemical industry.
[0074] like Figure 4 As shown, the Al-Al prepared in this embodiment 2 O 3 The average annual immersion corrosion rate of the -TPU hybrid corrosion-resistant coating was reduced by 78.43% and the erosion corrosion rate was reduced by 78.18% compared with the cold-sprayed Al single-element coating. This shows that adding Al to the Al-based coating 2 O 3 Ceramic particles and polymer TPU can greatly improve the coating's resistance to seawater corrosion and wear erosion.
[0075] like Figure 5 As shown, from Figure 5 (a) It can be seen that there are Al particles of different sizes and irregular shapes distributed in the Al-based coating. 2 O 3 The particles are embedded in the coating. In addition, surface defects such as cracks and holes are effectively filled due to the presence of TPU, which enhances the overall strength and toughness of the coating. Figure 5 As can be seen from the cross-sectional schematic diagram shown in (b), the Al dispersed in the Al-based coating 2 O 3 Ceramic particles can significantly enhance the overall mechanical properties and toughness. The internal local cracks and holes can improve the bonding strength between the coating and the substrate due to the filling of TPU. By filling the defects, a "bridging" effect is formed, which can effectively reduce the porosity of the coating, reduce the stress concentration caused by holes, and prevent further expansion of cracks, thereby improving the wear resistance and corrosion resistance of the coating and enhancing the coating's crack resistance.
[0076] The Al-Al prepared in this example 2 O 3-The bonding strength between the TPU hybrid corrosion-resistant coating and the substrate is 26.36Mpa. The high bonding strength is due to the special low-pressure cold spraying process and Al near-spherical powder, Al 2 O 3 The synergistic effect of irregular shaped powder and TPU powder. First, Al powder particles have good plastic deformation ability. Plastic deformation during the spraying process can fill the microscopic unevenness of the substrate surface; secondly, irregular shaped Al 2 O 3 The addition of particles can enhance the mechanical interlocking effect between the coating and the substrate; finally, the presence of TPU provides good flexibility and cushioning, can absorb stress and reduce the risk of cracking. Its advantages include not easy to peel off during use, providing more lasting wear protection; better resistance to mechanical shock and vibration; can effectively prevent the penetration of corrosive media; improve the overall stability and durability of the coating, and extend the service life of the substrate.
[0077] The mass fractions of the raw materials in the cold spray preformed powder in this embodiment are: 35% Al powder, 35% Al 2 O 3 Ceramic particles 35%, TPU powder 30%. Appropriate amount of TPU and Al 2 O 3 Ceramic particles can significantly improve the impact resistance and wear resistance of the coating, without causing the coating to be too soft due to excessive TPU, affecting the hardness and strength of the Al-based coating, and not being able to effectively fill the pores and defects in the Al-based coating due to too low a ratio, and thus failing to fully exert its advantages. In order to illustrate the advantages of the coating raw material selection and dosage in the present invention, coatings with different raw material ratios were prepared using the same preparation technology and process parameters, and their bonding strength was tested for illustration, as shown in Table 1.
[0078] Table 1 Coating properties prepared with different raw material ratios
[0079]
[0080] Example 2
[0081] The low pressure cold spraying method of this embodiment is used to prepare Al-Al 2 O 3 -TPU mixed corrosion resistant coating method, the method is:
[0082] S1. Substrate preparation: 316L stainless steel material is surface treated by grinding, polishing, cleaning, drying and sandblasting in sequence to obtain the substrate to be sprayed;
[0083] S2, Al powder, Al 2 O 3The ceramic particles and thermoplastic polyurethane TPU powder are mechanically mixed for 8 hours to obtain a cold spray preformed powder;
[0084] The Al powder has a particle size of 10 μm to 40 μm and a purity of ≥ 99.9%. 2 O 3 The ceramic powder is irregular polygonal in shape, with a particle size of 20μm to 50μm, a purity of ≥99.9%, and an oxygen content of O 2 ≤300PPM; the particle size of thermoplastic polyurethane TPU powder is 20μm~50μm, and the purity is ≥99.9%; the cold spray prefabricated powder is composed of the following raw materials by mass fraction: Al powder 35%, Al 2 O 3 35% ceramic particles, the rest is thermoplastic polyurethane TPU powder;
[0085] The cold spray preformed powder is composed of the following raw materials by mass fraction: 35% Al powder, 2 O 3 35% ceramic particles, the rest is thermoplastic polyurethane TPU powder;
[0086] S3, the preformed powder obtained in S2 is low-pressure cold sprayed onto the substrate to be sprayed obtained in S1, and after the coating is cooled and solidified, it is polished and corrected to obtain an Al-Al with an average thickness of 2 mm. 2 O 3 -TPU hybrid corrosion resistant coating;
[0087] The process parameters of the low-pressure cold spraying are: the working gas is compressed air, the carrier gas pressure is 0.2 MPa, the carrier gas temperature is 200° C., the nozzle is 20 mm away from the substrate, and the spraying speed is 60 g / min.
[0088] The Al-Al prepared in this example 2 O 3 -TPU hybrid corrosion-resistant coating has an annual average immersion corrosion rate of 0.012 mm / a and an annual average erosion corrosion rate of 0.013 mm / a; the coating has a porosity of 2.35%; the Al-Al 2 O 3 -The bonding strength between the TPU hybrid corrosion-resistant coating and the substrate is 23.62MPa.
[0089] The Al-Al prepared in this example 2 O 3 -TPU hybrid corrosion resistant coating can be used in marine engineering.
[0090] The mixed corrosion-resistant coating is made by mixing Al metal powder, metal oxide ceramic particles Al 2 O 3, high molecular thermoplastic polyurethane (TPU) powder are mixed evenly in a certain proportion to obtain pre-made powder for cold spraying, and then the pre-made powder is sprayed onto the surface of the substrate by a low-pressure cold spraying method to obtain a mixed corrosion-resistant coating. Al metal powder is mainly used as the main matrix of the coating. It has excellent corrosion resistance and can form a dense oxide film in the marine environment to improve the corrosion resistance of the coating. Al 2 O 3 Ceramic particles have extremely high hardness. When added to the coating as a reinforcing phase, they can significantly improve the strength, hardness and wear resistance of the coating. They can effectively resist erosion and wear from corrosive media such as mud and sand in the marine environment. TPU mainly acts as a binder and filler material. It melts during low-pressure cold spraying and fills the micropores and defects in the coating to improve the density of the coating, reduce the voids in the coating, and help prevent the penetration of corrosive media. In addition, its excellent flexibility and wear resistance can compensate for the brittleness of the aluminum-based coating itself, improve the wear resistance of the Al-based coating, and prevent cracks, peeling or coating failure under external impact or mechanical stress. The required equipment is simple and the process is convenient.
[0091] The Al-Al prepared in this example 2 O 3 -TPU hybrid corrosion resistant coating has the following advantages:
[0092] (1) Seawater corrosion resistance:
[0093] This composite coating performs well in the marine environment and can effectively resist corrosive media in seawater. It is particularly suitable for marine engineering, ships, offshore platforms and other fields.
[0094] (2) Long life protection:
[0095] The individual components of the coating work together to provide long-term effective protection, extending the service life of the substrate and reducing the frequency and cost of maintenance and replacement.
[0096] (3) Wide application areas:
[0097] In addition to marine engineering, this composite coating can also be used in aerospace, chemical equipment, energy industry and other fields that require high wear resistance, high corrosion resistance and high temperature performance, and has broad market prospects.
[0098] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing Al-Al2O3-TPU mixed corrosion-resistant coating by low-pressure cold spraying, characterized in that: The method is: S1. Substrate preparation: The substrate is subjected to surface treatment, and is sequentially ground, polished, cleaned, dried, and sandblasted to obtain a substrate to be sprayed; S2, mechanically mixing Al powder, Al2O3 ceramic particles, and thermoplastic polyurethane TPU powder to obtain cold spray preformed powder; S3, cold spraying the cold spray preformed powder obtained in S2 onto the substrate to be sprayed obtained in S1 at low pressure, and after the coating is cooled and solidified, grinding and correction are performed to obtain an Al-Al2O3-TPU mixed corrosion-resistant coating; The process parameters of the low-pressure cold spraying are: the working gas is compressed air, the carrier gas pressure is 0.2-0.5 MPa, the carrier gas temperature is 150-200° C., the nozzle is 10-20 mm away from the substrate, and the spraying speed is 30-60 g / min.
2. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The substrate described in S1 is 316L stainless steel material.
3. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The Al powder in S2 is a nearly spherical powder with a particle size of 10μm to 40μm and a purity of ≥99.9%; the Al2O3 ceramic particles are irregular particles with a particle size of 20μm to 50μm and a purity of ≥99.9%; the thermoplastic polyurethane TPU powder has a particle size of 20μm to 50μm and a purity of ≥99.9%.
4. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The cold spray preformed powder in S2 is composed of the following raw materials in mass fractions: 35% Al powder, 35% Al2O3 ceramic particles, and the remainder is thermoplastic polyurethane TPU powder.
5. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The mechanical mixing time in S2 is 8 hours.
6. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The average thickness of the Al-Al2O3-TPU mixed corrosion-resistant coating in S3 is 500 μm to 2 mm.
7. The method for preparing Al-Al2O3-TPU hybrid corrosion-resistant coating by low-pressure cold spraying according to claim 1, characterized in that: The annual average immersion corrosion rate of the Al-Al2O3-TPU mixed corrosion-resistant coating in S3 is 0.011-0.012 m / a, and the annual average erosion corrosion rate is 0.012-0.013 mm / a; the bonding strength between the Al-Al2O3-TPU mixed corrosion-resistant coating and the substrate is 23.62-26.36 MPa, and the porosity of the Al-Al2O3-TPU mixed corrosion-resistant coating is 2.35%-2.67%.
8. An application of an Al-Al2O3-TPU hybrid corrosion-resistant coating prepared by the method according to any one of claims 1 to 7, characterized in that: The Al-Al2O3-TPU hybrid corrosion-resistant coating is used in marine engineering.
Citation Information
Patent Citations
Alloy resin composite anticorrosion coating for steel structure in maritime work environment and construction process thereof
CN102774112A
Aluminum oxide ceramic coating and preparation method thereof
CN109440051A
Low-pressure cold spraying Al-based coating surface in-situ ceramization method
CN111172526A
Spray mortar insulation for engine room, deck house wall and pipe in all vessel
KR101465336B1
Electrodeposited, Nanolaminate Coatings and Claddings for Corrosion Protection
US20120088118A1